A method for increasing the heat resistance temperature of pure aluminum wire

The high-strength and ultra-heat-resistant pure aluminum conductor is prepared through the powder extrusion and sintering process, which solves the problem of insufficient heat resistance temperature of existing aluminum alloys, achieves heat resistance of 300°C and excellent mechanical properties, and is suitable for ultra-high voltage transmission lines.

CN119407177BActive Publication Date: 2025-09-23YANTAI ADVANCED MATERIALS & GREEN MFG SHANDONG PROVINCIAL LAB +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411566416.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-09-23
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

The long-term operating temperature of existing high-strength, high-conductivity, heat-resistant aluminum alloys is only 200°C, which makes it difficult to meet service requirements at higher temperatures.

Method used

A powder extrusion and sintering process is used, including high-energy ball milling, isostatic pressing, hot extrusion sintering, heat treatment and multi-pass drawing, to prepare high-strength and ultra-heat-resistant pure aluminum wires.

Benefits of technology

The heat resistance temperature of pure aluminum wires has been significantly increased to 300°C, and their yield strength, tensile strength and electrical conductivity have been improved, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119407177B_ABST
    Figure CN119407177B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for improving the heat resistance temperature of pure aluminum conductors, belonging to the technical field of improving the performance of pure aluminum conductors. The method adopts a powder extrusion and sintering process, specifically comprising the following steps: using ethanol and / or dry ice as an anti-forging agent to high-energy ball mill pure aluminum powder to obtain ultrafine pure aluminum powder with an average grain size of 100nm-250nm, a clean surface and high activity, isostatically pressing the ultrafine pure aluminum powder to obtain a preform, hot extruding and sintering the preform to obtain a high-strength aluminum rod, and then subjecting the high-strength aluminum rod to front-end grinding, deburring, heat treatment, wire drawing and annealing to obtain a pure aluminum conductor. The benefits of the present invention are that the yield strength and tensile strength of the prepared pure aluminum conductor are relatively strong, and the heat resistance temperature is increased from the current 200°C to 300°C. It is a high-strength and ultra-heat-resistant pure aluminum conductor, which is expected to be widely used in the construction of ultra-high voltage transmission lines.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for improving the heat-resistant temperature of a pure aluminum conductor, belonging to the technical field of improving the performance of a pure aluminum conductor. Background Art

[0002] Electricity is the main energy source for most industrial activities. With the increase in human electricity consumption, people have an increasing demand for safe, reliable and efficient long-distance overhead power transmission lines that can carry large currents.

[0003] Compared with other metal materials, aluminum wire has good mechanical and electrical properties, high strength-to-weight ratio and low cost, so it is widely used in long-distance transmission lines.

[0004] Chinese patent CN201410482230.6 discloses a method for preparing a high-strength, high-conductivity, heat-resistant aluminum alloy. The high-strength, high-conductivity, heat-resistant aluminum alloy prepared by the method does not contain any other alloying elements except aluminum. The room temperature tensile strength of the material can reach 200 MPa, the elongation is 20%, the conductivity is above 61 IACS%, and the long-term operating temperature can reach 200°C.

[0005] Higher operating temperature is one of the important tests that overhead conductors face during their service. The long-term operating temperature of existing high-strength, high-conductivity, heat-resistant aluminum alloys is only 200°C, which needs to be further improved. Summary of the Invention

[0006] In order to solve the deficiencies of the prior art, the present invention aims to provide a method for increasing the heat-resistant temperature of pure aluminum wires.

[0007] In order to achieve the above objectives, the present invention adopts the following technical solutions:

[0008] A method for increasing the heat resistance temperature of a pure aluminum conductor, using a powder extrusion sintering process, specifically comprising the following steps:

[0009] (1) High-energy ball milling: steel balls and pure aluminum powder are placed in a ball mill, ethanol and / or dry ice are added as an anti-forging agent, and high-energy ball milling is performed for 50 h to 80 h to obtain ultrafine pure aluminum powder with an average grain size of 100 nm to 250 nm, a clean surface, and high activity;

[0010] (2) isostatic pressing: isostatically pressing the ultrafine pure aluminum powder obtained in step (1) at a pressure of 250 MPa to 350 MPa, maintaining the pressure for 5 min to 15 min to obtain a preform;

[0011] (3) Hot extrusion sintering: The preform obtained in step (2) is subjected to hot extrusion sintering using an extruder, wherein the extruder pressure is 500 tons to 1300 tons, the extrusion ratio is 10-120:1, the temperature of the extrusion barrel and the mold is 380°C to 550°C, and the hot extrusion is carried out in two steps. The first step is pressurized compaction with a compaction pressure of 1100 tons to 1250 tons, and the second step is extrusion to obtain a high-strength aluminum rod;

[0012] (4) Grinding and removing burrs: Grind the high-strength aluminum rod obtained in step (3) at the front end with a sharpening machine, and remove the burrs with sandpaper;

[0013] (5) Heat treatment: heat treatment is performed on the high-strength aluminum rod obtained in step (4), the heat treatment temperature is 200° C.-500° C., and the treatment time is 0.5 h-3 h;

[0014] (6) Wire drawing: The high-strength aluminum rod obtained in step (5) is subjected to multiple drawing passes, with the deformation of each drawing pass being 3%-5%. Each drawing pass requires intermediate annealing, with the annealing temperature being 200°C-400°C and the annealing time being 5min-30min, until a wire with a diameter of 0.5mm-5.0mm is obtained;

[0015] (7) Annealing treatment: The wire obtained in step (6) is annealed at a temperature of 100°C to 350°C for a time of 1.5 hours to 3 hours to obtain a pure aluminum wire having a heat-resistant temperature of 300°C.

[0016] Preferably, in step (2), isostatic pressing is performed at a pressure of 250 MPa-350 MPa, and the pressure is maintained for 12 min-15 min.

[0017] Preferably, in step (3), the extruder pressure is 1150 tons to 1300 tons, the extrusion ratio is 80-120:1, the temperature of the extrusion barrel and the mold is 400°C to 550°C, and the compaction pressure is 1200 tons to 1250 tons.

[0018] Preferably, in step (5), the heat treatment temperature is 400° C.-500° C., and the treatment time is 0.5 h-2 h.

[0019] Preferably, in step (6), the annealing temperature is 300° C.-400° C., the annealing time is 25 min-30 min, and the diameter of the wire is 0.5 mm-1.5 mm.

[0020] Preferably, in step (7), the annealing temperature is 300° C.-350° C., and the annealing time is 2.5 h-3 h.

[0021] The present invention is beneficial in that:

[0022] (1) By subjecting aluminum powder to high-energy ball milling under specified process parameters, in addition to producing nano-scale Al2O3 dispersed oxides, high-density nano-stacked faults are also produced (with extremely high thermodynamic stability, which can be retained during subsequent hot extrusion and drawing processes). The high-density nano-stacked faults produced by high-energy ball milling not only further improve the mechanical properties (yield strength and tensile strength) of the pure aluminum wire, but more importantly, increase the heat resistance temperature of the pure aluminum wire from the current 200°C to 300°C, significantly improving the heat resistance of the pure aluminum wire;

[0023] (2) The preform obtained after isostatic pressing does not need to be sintered into blocks first but is directly hot extruded at 380°C-550°C. During the hot extrusion process, extrusion and sintering densification are completed simultaneously, breaking the conventional operation in this field, simplifying the production steps, and greatly saving production costs;

[0024] (3) By hot extrusion sintering the preform, columnar crystals and coarse grains are eliminated, and a large number of micro-nanoscale grains are obtained. These micro-nanoscale grains improve the mechanical properties (yield strength and tensile strength) of the pure aluminum wire while ensuring the electrical conductivity of the pure aluminum wire;

[0025] (4) The pure aluminum conductor prepared by the powder extrusion sintering process of the present invention is a high-strength and particularly heat-resistant pure aluminum conductor, with a yield strength of 263MPa-296MPa, a tensile strength of 285MPa-320MPa, an elongation of 4.7%-5.6%, and an electrical conductivity of 50.3IACS%-53.5IACS%. The strength retention rate after running at 300°C for 400h reaches 96.7%-98.2%, and the heat-resistant temperature is increased from the current 200°C to 300°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is a transmission electron microscope photograph of a pure aluminum conductor 1;

[0027] Figure 2 is a transmission electron microscope photograph of pure aluminum wire 2;

[0028] Figure 3 is a transmission electron microscope photograph of a pure aluminum conductor 3;

[0029] Figure 4 is a transmission electron microscope photograph of a pure aluminum conductor 4;

[0030] Figure 5 This is an electron backscatter diffraction photograph of a pure aluminum wire 5;

[0031] Figure 6 is a transmission electron microscope photograph of a pure aluminum conductor 6;

[0032] Figure 7is a transmission electron microscope photograph of a pure aluminum conductor 7;

[0033] Figure 8 8 is an element distribution diagram of a pure aluminum conductor. DETAILED DESCRIPTION

[0034] The present invention will be described in detail below with reference to the accompanying drawings and specific embodiments.

[0035] Example 1

[0036] Steel balls and 1000g of pure aluminum powder were placed in a ball mill at a ball-to-material ratio of 10:1. 24mL of ethanol was added as an anti-forging agent. The steel balls were vibrated at an amplitude of 4mm and a frequency of 1450 cpm for 80 hours of high-energy ball milling. This yielded a clean, highly active ultrafine aluminum powder (which provided the foundation for subsequent hot extrusion, sintering, and wire drawing). Testing revealed a purity of >99.5% and an average grain size of 100nm.

[0037] The high-activity ultrafine pure aluminum powder obtained above was isostatically pressed at a pressure of 350 MPa with a holding time of 15 minutes to obtain a preform.

[0038] The preform obtained above was hot extruded using an extruder, and sintering and densification were simultaneously completed during the hot extrusion process. The extruder pressure was 1,300 tons, the extrusion ratio was 120:1, and the temperature of the extrusion barrel and the mold was 550°C. In order to obtain an aluminum rod with uniform performance and density, hot extrusion was carried out in two steps: the first step was pressurized compaction, and the second step was extrusion. The pressurized compaction operation was as follows: the preform was placed inside the extrusion barrel and pressurized compaction was performed through the solid plug in the three-station. The compaction pressure was 1,250 tons to obtain a high-strength aluminum rod.

[0039] The high-strength aluminum rod obtained above was ground into a finer shape at the front end using a sharpening machine, and the burrs were removed using sandpaper.

[0040] The high-strength aluminum rod obtained above was heat treated at a temperature of 500° C. for 0.5 h.

[0041] The high-strength aluminum rod that has been heat-treated is drawn in multiple passes until a wire with a diameter of 0.5 mm is obtained, wherein the deformation of each drawing pass is 5%, and each drawing pass requires intermediate annealing at an annealing temperature of 400°C and an annealing time of 30 minutes.

[0042] The wire obtained above was annealed at a temperature of 350° C. for 3 h to obtain a pure aluminum wire 1 , which showed no defects when inspected internally.

[0043] Example 2

[0044] Steel balls and 1000g of pure aluminum powder were placed in a ball mill at a ball-to-material ratio of 10:1. 30g of dry ice was added as an anti-forging agent. The steel balls were vibrated at an amplitude of 4mm and a frequency of 1450 cpm for 70 hours. This resulted in ultrafine aluminum powder with a clean surface and high activity. Testing revealed an average grain size of 150nm.

[0045] The high-activity ultrafine pure aluminum powder obtained above was isostatically pressed at a pressure of 300 MPa with a holding time of 15 minutes to obtain a preform.

[0046] The preform obtained above was hot extruded using an extruder, and sintering and densification were simultaneously completed during the hot extrusion process. The extruder pressure was 1250 tons, the extrusion ratio was 100:1, and the temperature of the extrusion barrel and the mold was 500°C during the extrusion and sintering process. The hot extrusion was carried out in two steps, the first step was pressurized compaction, and the second step was extrusion. The pressurized compaction operation was as follows: the preform was placed inside the extrusion barrel, and pressurized compaction was performed through the solid plug in the three-station. The compaction pressure was 1200 tons to obtain a high-strength aluminum rod.

[0047] The high-strength aluminum rod obtained above was ground into a finer shape at the front end using a sharpening machine, and the burrs were removed using sandpaper.

[0048] The high-strength aluminum rod obtained above was heat treated at a temperature of 500° C. for 1 h.

[0049] The high-strength aluminum rod that has been heat-treated is drawn in multiple passes until a wire with a diameter of 1.0 mm is obtained, wherein the deformation of each drawing pass is 5%, and each drawing pass requires intermediate annealing at an annealing temperature of 400°C and an annealing time of 30 minutes.

[0050] The wire material obtained above was annealed at a temperature of 300° C. for 2.5 h to obtain a pure aluminum wire 2 , which showed no defects when inspected internally.

[0051] Example 3

[0052] Steel balls and 1000g of pure aluminum powder were placed in a ball mill at a ball-to-material ratio of 11:1. 15mL of ethanol and 20g of dry ice were added as anti-forging agents. The steel balls were vibrated at an amplitude of 4mm and a frequency of 1460 cpm for 60 hours. This resulted in ultrafine pure aluminum powder with a clean surface and high activity. Testing revealed an average grain size of 200nm.

[0053] The high-activity ultrafine pure aluminum powder obtained above was isostatically pressed at a pressure of 280 MPa with a holding time of 12 minutes to obtain a preform.

[0054] The preform obtained above was hot extruded using an extruder, and sintering and densification were simultaneously completed during the hot extrusion process. The extrusion pressure was 1200 tons, the extrusion ratio was 90:1, the temperature of the extrusion barrel and the mold was 450°C, and the hot extrusion was carried out in two steps: the first step was pressurization and compaction, and the second step was extrusion. The pressurization and compaction operation was as follows: the preform was placed inside the extrusion barrel, and pressurized and compacted through the solid plug in the three-station. The compaction pressure was 1200 tons to obtain a high-strength aluminum rod.

[0055] The high-strength aluminum rod obtained above was ground into a finer shape at the front end using a sharpening machine, and the burrs were removed using sandpaper.

[0056] The high-strength aluminum rod obtained above was heat treated at a temperature of 400° C. for 1.5 h.

[0057] The high-strength aluminum rod that has been heat-treated is drawn in multiple passes until a wire with a diameter of 1.5 mm is obtained, wherein the deformation of each drawing pass is 5%, and each drawing pass requires intermediate annealing at an annealing temperature of 400°C and an annealing time of 25 minutes.

[0058] The wire obtained above was annealed at a temperature of 300° C. for 2.5 h to obtain a pure aluminum wire 3 , which showed no defects when inspected internally.

[0059] Example 4

[0060] Steel balls and 1000g of pure aluminum powder were placed in a ball mill at a ball-to-material ratio of 11:1. 30mL of ethanol was added as an anti-forging agent. The steel balls were vibrated at an amplitude of 5mm and a frequency of 1460 cpm for 50 hours. This resulted in ultrafine aluminum powder with a clean surface and high activity. Testing revealed an average grain size of 250nm.

[0061] The high-activity ultrafine pure aluminum powder obtained above was isostatically pressed at a pressure of 250 MPa with a holding time of 12 minutes to obtain a preform.

[0062] The preform obtained above was hot extruded using an extruder, and sintering and densification were simultaneously completed during the hot extrusion process. The extruder pressure was 1150 tons, the extrusion ratio was 80:1, the temperature of the extrusion barrel and the mold was 400°C, and the hot extrusion was carried out in two steps: the first step was pressurized compaction, and the second step was extrusion. The pressurized compaction operation was as follows: the preform was placed inside the extrusion barrel, and pressurized compaction was performed through the solid plug in the three-station. The compaction pressure was 1250 tons to obtain a high-strength aluminum rod.

[0063] The high-strength aluminum rod obtained above was ground into a finer shape at the front end using a sharpening machine, and the burrs were removed using sandpaper.

[0064] The high-strength aluminum rod obtained above was heat treated at a temperature of 400°C for 2 hours.

[0065] The high-strength aluminum rod that has been heat-treated is drawn in multiple passes until a wire with a diameter of 0.5 mm is obtained, wherein the deformation of each drawing pass is 4%, and each drawing pass requires intermediate annealing at an annealing temperature of 300°C and an annealing time of 30 minutes.

[0066] The wire material obtained above was annealed at a temperature of 350° C. for 3 h to obtain a pure aluminum wire 4 , which showed no defects when inspected internally.

[0067] Example 5

[0068] Steel balls and 1000g of pure aluminum powder were placed in a ball mill at a ball-to-material ratio of 12:1. 20mL of ethanol and 10g of dry ice were added as anti-forging agents. The steel balls were vibrated at an amplitude of 5mm and a frequency of 1470 cpm for 50 hours. This resulted in ultrafine pure aluminum powder with a clean surface and high activity. Testing revealed an average grain size of 290nm.

[0069] The high-activity ultrafine pure aluminum powder obtained above was isostatically pressed at a pressure of 280 MPa with a holding time of 9 minutes to obtain a preform.

[0070] The preform obtained above was hot extruded using an extruder, and sintering and densification were simultaneously completed during the hot extrusion process. The extrusion pressure was 1000 tons, the extrusion ratio was 60:1, the temperature of the extrusion barrel and the mold was 380°C, and the hot extrusion was carried out in two steps: the first step was pressurized compaction, and the second step was extrusion. The pressurized compaction operation was as follows: the preform was placed inside the extrusion barrel, and pressurized compaction was performed through the solid plug in the three-station. The compaction pressure was 1200 tons to obtain a high-strength aluminum rod.

[0071] The high-strength aluminum rod obtained above was ground into a finer shape at the front end using a sharpening machine, and the burrs were removed using sandpaper.

[0072] The high-strength aluminum rod obtained above was heat treated at a temperature of 400° C. for 1 h.

[0073] The high-strength aluminum rod that has been heat-treated is drawn in multiple passes until a wire with a diameter of 2.9 mm is obtained, wherein the deformation of each drawing pass is 4%, and each drawing pass requires intermediate annealing at an annealing temperature of 350°C and an annealing time of 20 minutes.

[0074] The wire material obtained above was annealed at a temperature of 200° C. for 1.5 h to obtain a pure aluminum wire 5 , which showed no defects when inspected internally.

[0075] Example 6

[0076] Steel balls and 1000g of pure aluminum powder were placed in a ball mill at a ball-to-material ratio of 12:1. 40g of dry ice was added as an anti-forging agent. The steel balls were vibrated at an amplitude of 5mm and a frequency of 1470 cpm for 40 hours. This resulted in ultrafine pure aluminum powder with a clean surface and high activity. Testing revealed an average grain size of 320nm.

[0077] The high-activity ultrafine pure aluminum powder obtained above was isostatically pressed at a pressure of 300 MPa with a holding time of 9 minutes to obtain a preform.

[0078] The preform obtained above was hot extruded using an extruder, and sintering and densification were simultaneously completed during the hot extrusion process. The extruder pressure was 900 tons, the extrusion ratio was 60:1, the temperature of the extrusion barrel and the mold was 380°C, and the hot extrusion was carried out in two steps: the first step was pressurized compaction, and the second step was extrusion. The pressurized compaction operation was as follows: the preform was placed inside the extrusion barrel, and pressurized compaction was performed through the solid plug in the three-station. The compaction pressure was 1200 tons to obtain a high-strength aluminum rod.

[0079] The high-strength aluminum rod obtained above was ground into a finer shape at the front end using a sharpening machine, and the burrs were removed using sandpaper.

[0080] The high-strength aluminum rod obtained above was heat treated at a temperature of 300° C. for 2 h.

[0081] The high-strength aluminum rod that has been heat-treated is drawn in multiple passes until a wire with a diameter of 3.0 mm is obtained, wherein the deformation of each drawing pass is 4%, and each drawing pass requires intermediate annealing at an annealing temperature of 300°C and an annealing time of 30 minutes.

[0082] The wire obtained above was annealed at a temperature of 100° C. for 3 h to obtain a pure aluminum wire 6 , which showed no defects when inspected internally.

[0083] Example 7

[0084] Steel balls and 1000g of pure aluminum powder were placed in a ball mill at a ball-to-material ratio of 12:1. 20mL of ethanol and 20g of dry ice were added as anti-forging agents. The steel balls were vibrated at an amplitude of 6mm and a frequency of 1480 cpm for 30 hours of high-energy ball milling. This yielded ultrafine pure aluminum powder with a clean surface and high activity. Testing revealed an average grain size of 390nm.

[0085] The high-activity ultrafine pure aluminum powder obtained above was isostatically pressed at a pressure of 320 MPa with a holding time of 5 minutes to obtain a preform.

[0086] The preform obtained above was hot extruded using an extruder, and sintering and densification were simultaneously completed during the hot extrusion process. The extruder pressure was 600 tons, the extrusion ratio was 30:1, the temperature of the extrusion barrel and the mold was 450°C, and the hot extrusion was carried out in two steps: the first step was pressurized compaction, and the second step was extrusion. The pressurized compaction operation was as follows: the preform was placed inside the extrusion barrel, and pressurized compaction was performed through the solid plug in the three-station. The compaction pressure was 1100 tons to obtain a high-strength aluminum rod.

[0087] The high-strength aluminum rod obtained above was ground into a finer shape at the front end using a sharpening machine, and the burrs were removed using sandpaper.

[0088] The high-strength aluminum rod obtained above was heat treated at a temperature of 200° C. for 3 h.

[0089] The high-strength aluminum rod that has been heat-treated is drawn in multiple passes until a wire with a diameter of 5.0 mm is obtained, wherein the deformation of each drawing pass is 3%, and each drawing pass requires intermediate annealing at an annealing temperature of 200°C and an annealing time of 15 minutes.

[0090] The wire material obtained above was annealed at a temperature of 350° C. for 3 h to obtain a pure aluminum wire 7 , which showed no defects when inspected internally.

[0091] Example 8

[0092] Steel balls and 1000g of pure aluminum powder were placed in a ball mill at a ball-to-powder ratio of 12:1. 40mL of ethanol was added as an anti-forging agent. The steel balls were vibrated at an amplitude of 6mm and a frequency of 1490 cpm for 20 hours. This resulted in ultrafine pure aluminum powder with a clean surface and high activity. Testing revealed an average grain size of 450nm.

[0093] The high-activity ultrafine pure aluminum powder obtained above was isostatically pressed at a pressure of 350 MPa with a holding time of 5 minutes to obtain a preform.

[0094] The preform obtained above was hot extruded using an extruder, and sintering and densification were simultaneously completed during the hot extrusion process. The extruder pressure was 500 tons, the extrusion ratio was 10:1, the temperature of the extrusion barrel and the mold was 400°C, and the hot extrusion was carried out in two steps. The first step was pressurized compaction, and the second step was extrusion. The pressurized compaction operation was as follows: the preform was placed inside the extrusion barrel, and pressurized compaction was performed through the solid plug in the three-station. The compaction pressure was 1100 tons to obtain a high-strength aluminum rod.

[0095] The high-strength aluminum rod obtained above was ground into a finer shape at the front end using a sharpening machine, and the burrs were removed using sandpaper.

[0096] The high-strength aluminum rod obtained above was heat treated at a temperature of 200° C. for 3 h.

[0097] The high-strength aluminum rod that has been heat-treated is drawn in multiple passes until a wire with a diameter of 5.0 mm is obtained, wherein the deformation of each drawing pass is 3%, and each drawing pass requires intermediate annealing at an annealing temperature of 200° C. and an annealing time of 5 minutes.

[0098] The wire obtained above was annealed at a temperature of 350° C. for 3 h to obtain a pure aluminum wire 8 , which showed no defects when inspected internally.

[0099] The yield strength (room temperature), tensile strength (room temperature), elongation (room temperature), electrical conductivity (room temperature), strength retention after 400 hours of operation at 300°C, and heat resistance temperature of the pure aluminum wires 1, 2, 3, 4, 5, 6, 7, and 8 obtained above were tested. The test results are shown in Table 1.

[0100] Table 1 Test results of yield strength, tensile strength, electrical conductivity and heat resistance temperature of pure aluminum wire

[0101]

[0102]

[0103] As shown in Table 1, the pure aluminum conductor prepared by the present invention has a yield strength of 233 MPa-296 MPa, a tensile strength of 250 MPa-320 MPa, an elongation of 4.7%-6.1%, and an electrical conductivity of 52.3 IACS%-56.1 IACS%. The strength retention rate after operation at 300°C for 400 hours reaches 96.5%-98.2%, and the heat resistance temperature reaches 300°C (the heat resistance temperature of the current 6201 high-strength aluminum alloy conductor is 150°C, and the long-term use temperature of the high-strength, high-conductivity, heat-resistant aluminum alloy disclosed in Chinese patent CN201410482230.6 is 200°C). It is a high-strength, high-heat-resistant pure aluminum conductor. Among them, pure aluminum conductor 1, pure aluminum conductor 2, pure aluminum conductor 3, and pure aluminum conductor 4 have better performance. These conductors are expected to be widely used in the construction of ultra-high voltage transmission lines.

[0104] Transmission electron microscope photos of pure aluminum wire 1, pure aluminum wire 2, pure aluminum wire 3, pure aluminum wire 4, pure aluminum wire 6 and pure aluminum wire 7 are shown in FIG. Figure 1 、 Figure 2 、 Figure 3 、 Figure 4 、 Figure 6 and Figure 7 , the electron backscatter diffraction photo of pure aluminum wire 5 is shown in Figure 5, the element distribution diagram of pure aluminum conductor 8 is shown in Figure 8 ,in, Figure 6 Spherical nano-scale aluminum oxide can be observed. Figure 7 High density of nano-stacking faults can be observed. Figure 8 Obvious oxygen segregation can be observed (indicating the presence of oxides).

[0105] The pure aluminum wire prepared by the present invention has the characteristics of high strength and high heat resistance because:

[0106] (1) During the high-energy ball milling process under specified process parameters, not only nano-scale Al2O3 dispersed oxides are produced (which can pin dislocations and grain boundaries and hinder their movement), but also high-density nano-stacked faults are produced (which have extremely high thermodynamic stability and can be retained during subsequent hot extrusion and drawing processes). These two factors effectively enhance the mechanical properties (yield strength and tensile strength) and heat resistance of pure aluminum wires.

[0107] (2) During the hot extrusion process, a large amount of plastic flow is generated, which eliminates columnar crystals and coarse grains, and finally obtains a large number of micro-nanoscale grains. These micro-nanoscale grains improve the mechanical properties (yield strength and tensile strength) of the pure aluminum wire while ensuring the electrical conductivity of the pure aluminum wire.

[0108] It should be noted that the above embodiments are merely examples for the purpose of clearly illustrating the present invention and are not intended to limit the embodiments of the present invention. A person skilled in the art would be able to make other variations or modifications based on the above description. It is not possible to enumerate all embodiments here. Any obvious variations or modifications arising from the technical solution of the present invention remain within the scope of protection of the present invention.

Claims

1. A method for increasing the heat resistance temperature of a pure aluminum wire, characterized in that: The powder extrusion sintering process is adopted, which specifically includes the following steps: (1) High-energy ball milling: steel balls and pure aluminum powder are placed in a ball mill, ethanol and / or dry ice are added as an anti-forging agent, and high-energy ball milling is performed for 50 h to 80 h to obtain ultrafine pure aluminum powder with an average grain size of 100 nm to 250 nm, a clean surface, and high activity; (2) isostatic pressing: isostatically pressing the ultrafine pure aluminum powder obtained in step (1) at a pressure of 250 MPa to 350 MPa, maintaining the pressure for 5 min to 15 min to obtain a preform; (3) Hot extrusion sintering: The preform obtained in step (2) is subjected to hot extrusion sintering using an extruder, wherein the extruder pressure is 500 tons to 1300 tons, the extrusion ratio is 10-120:1, the temperature of the extrusion barrel and the mold is 380°C to 550°C, and the hot extrusion is carried out in two steps. The first step is pressurized compaction with a compaction pressure of 1100 tons to 1250 tons, and the second step is extrusion to obtain a high-strength aluminum rod; (4) Grinding and removing burrs: Grind the high-strength aluminum rod obtained in step (3) at the front end with a sharpening machine, and remove the burrs with sandpaper; (5) Heat treatment: heat treatment is performed on the high-strength aluminum rod obtained in step (4), the heat treatment temperature is 200° C.-500° C., and the treatment time is 0.5 h-3 h; (6) Wire drawing: The high-strength aluminum rod obtained in step (5) is subjected to multiple drawing passes, with the deformation of each drawing pass being 3%-5%. Each drawing pass requires intermediate annealing, with the annealing temperature being 200°C-400°C and the annealing time being 5min-30min, until a wire with a diameter of 0.5mm-5.0mm is obtained; (7) Annealing treatment: The wire obtained in step (6) is annealed at a temperature of 100°C to 350°C for a time of 1.5 hours to 3 hours to obtain a pure aluminum wire having a heat-resistant temperature of 300°C.

2. The method for increasing the heat resistance temperature of pure aluminum wire according to claim 1, characterized in that: In step (2), the pressure is maintained for 12-15 minutes.

3. The method for increasing the heat resistance temperature of pure aluminum wire according to claim 1, characterized in that: In step (3), the extruder pressure is 1150 tons to 1300 tons, the extrusion ratio is 80-120:1, the temperature of the extrusion barrel and the mold is 400°C to 550°C, and the compaction pressure is 1200 tons to 1250 tons.

4. The method for increasing the heat resistance temperature of a pure aluminum conductor according to claim 1, wherein: In step (5), the heat treatment temperature is 400°C-500°C, and the treatment time is 0.5h-2h.

5. The method for increasing the heat resistance temperature of a pure aluminum conductor according to claim 1, wherein: In step (6), the annealing temperature is 300° C.-400° C., the annealing time is 25 min-30 min, and the diameter of the wire is 0.5 mm-1.5 mm.

6. The method for increasing the heat resistance temperature of pure aluminum wire according to claim 1, characterized in that: In step (7), the annealing temperature is 300° C.-350° C., and the annealing time is 2.5 h-3 h.

Citation Information

Patent Citations

  • Method for preparing high-strength, high-conductivity and heat-resistant aluminum alloys

    CN104263983A

  • Preparation method for heat-resistant aluminium alloy

    CN105695785A

  • High-density and high-carbon-content aluminum-based composite material and preparation method thereof

    CN117626042A